(untitled) (Nexo Revista Científica, 2011)
In this work, the adsorption kinetic of Cu(II) and Hg(II) onto chitosan was studied from a binary solution at different initial concentration of metallic ions, at different particle sizes and agitation rate. Chitosan was obtained from shrimp shells. Solutions of 1 L of Cu(II) and Hg(II) were placed in contact with 2 g of chitosan and the mixture was agitated by 8 h. Afterwards, the samples were analysed by atomic absorption. The experimental data were tested by application of kinetic models of pseudo-first order and pseudo-second order. The results of adsorption process showed that in the most cases, both ions were effectively adsorbed by chitosan. The percentage of adsorption was 43-100 % and 94-100 % for Cu(II) and Hg(II), respectively. The results also showed that at low concentrations, experimental data were better adjusted by pseudo-first order models; meanwhile, at high concentration, the data were well described by the pseudo-second model. Therefore, the rate-limiting step is the adsorption reaction and not mass transfer. Keywords: Adsorption kinetics; Binary solution; Chitosan; Kinetic models; Shrimp shell DOI: http://dx.doi.org/10.5377/nexo.v24i1.591 Nexo, Vol. 24, No. 1, pp. 20-32, 2011